Sustainable Tourism as a Strategic Rural Development: A Case Study in Indonesia - Sasongko, Ibnu; Trisandini Azzizi, Vidya (KnE Social Sciences, 2024)
Recently, efforts to promote equity development and reduce the rural-urban gap have been made, such as the development of optimizing rural tourism to increase job opportunities, therefore improving overall rural economic conditions. Agritourism presents the best chance for rural areas to sustainably develop as it would fulfill environmental, economic, and social wellbeing when properly implemented. This research aimed to develop rural tourism that utilizes local culture and resources while prioritizing sustainable development in Pujon Kidul, Malang Regency, Indonesia. Qualitative descriptive methods were adopted for this study and included land suitability analysis with Visual Absorption Capability (VAC), community attitude analysis with Irridex, linkage system and integrated system. Proper rural tourism management that considers environmental, social, and economic aspects may prevent the exploitation of available resources and thus promote sustainable development in a rural context. Keywords: rural tourism, Visual Absorption Capability, sustainable development